Perindopril decreases P wave dispersion in patients with stage 1 hypertension - FAK, ALİ SERDAR; ÖZBEN SADIÇ, BESTE (SAGE PUBLICATIONS LTD, 2009)
Introduction. Angiotensin-converting enzyme inhibitors prevent atrial fibrillation episodes by effective control of blood pressure and improving electrical and structural remodelling in the atria. Increased P wave dispersion (PWD) is a non-invasive electrocardiographic marker for paroxysmal atrial fibrillation. The aim of the study was to evaluate the effect of perindopril treatment on PWD in hypertensive patients. Methods. Forty-eight hypertensive patients (mean age 57.4 +/- 11.8 years, 18 men) were included. Blood pressure values were determined and 12-lead electrocardiograms were recorded at the beginning and at the first week, first month, third month and sixth month of the perindopril treatment. The difference between maximum and minimum P wave durations was calculated as PWD. Results. PWDs were significantly shortened at the first, third and sixth months (41.7 +/- 8.8 ms, 39-1 +/- 6.9 ms and 38.3 +/- 7.1 ms, respectively) compared with baseline and first-week measurements (54.3 +/- 9.2 ms and 49.0 +/- 9.1 ms, respectively, p<0.001). Baseline PWD was correlated with body mass index (r=0.32, p=0.026), while PWD at the sixth month of treatment was significantly correlated with left atrial volume index (r=0.30, p=0.042). Multiple linear regression analysis revealed that PWD at the sixth month was related to baseline PWD (p=0.001). Conclusion. Perindopril treatment significantly reduced PWD in hypertensive patients.
Keywords: angiotensin-converting enzyme inhibitor; atrial fibrillation; electrocardiography; hypertension; perindopril; P wave dispersion; PAROXYSMAL ATRIAL-FIBRILLATION; ANGIOTENSIN-CONVERTING ENZYME; LEFT-VENTRICULAR DYSFUNCTION; POPULATION-BASED COHORT; HEART-FAILURE; RISK-FACTORS; SINUS RHYTHM; FOLLOW-UP; LOSARTAN; INHIBITION